2015
DOI: 10.3389/fpsyg.2015.01591
|View full text |Cite
|
Sign up to set email alerts
|

Measuring creative imagery abilities

Abstract: Over the decades, creativity and imagination research developed in parallel, but they surprisingly rarely intersected. This paper introduces a new theoretical model of creative visual imagination, which bridges creativity and imagination research, as well as presents a new psychometric instrument, called the Test of Creative Imagery Abilities (TCIA), developed to measure creative imagery abilities understood in accordance with this model. Creative imagination is understood as constituted by three interrelated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 63 publications
0
54
0
7
Order By: Relevance
“…A statistically insignificant increase was observed during the study in the control group. This situation showed that the development of the children's creative imagination increased together with their experiences (Gündoğan, 2019;Jankowska & Karwowski, 2015;Semenovich Vygotsky, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…A statistically insignificant increase was observed during the study in the control group. This situation showed that the development of the children's creative imagination increased together with their experiences (Gündoğan, 2019;Jankowska & Karwowski, 2015;Semenovich Vygotsky, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…Although a number of measures exist that assess constructs similar to imagination, these measures generally approach imagination as the ability to conjure mental imagery, or view imagination as a component of creative ability (e.g., Jankowska & Karwowski, 2015, Marks, 1973. One of the exceptions is the Imaginal Processes Inventory (Singer & Antrobus, 1966), however its administration is time-consuming (344 items), and some of its features may not be entirely relevant to imagination (e.g., acceptance and distractibility).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some measures of mental imagery and creative imagination assess the ability for imagery with measures akin to divergent thinking tests (e.g., Torrance, 1974). These measures instruct participants to generate images from incomplete figures, with responses scored for vividness, originality, and transformative ability (Jankowska & Karwowski, 2015). Another self-report instrument attempts to quantify participants' evaluations of their own imagination, encompassing satisfaction, implementation, learning, and process (Jung, Flores, & Hunter, 2016).…”
mentioning
confidence: 99%
“…The Test of Creative Imagery Abilities (TCIA; Jankowska & Karwowski, 2015) was used to examine the role of imagination in friendships. It was found that students with higher scores on the TCIA were more likely to be nominated as a friend by their peers (McKay, Grygiel, & imagination was related to introspection and conformity, as well as to creativity and art appreciation.…”
Section: Key Research Findings On the Described Measuresmentioning
confidence: 99%
“…HIQ (Jung et al, 2016) is a suitable instrument for studying imagination over time (4 separate sessions, 3-7 days apart), while the TCIA (Jankowska & Karwowski, 2015) is a performance-based measure of imagination that differentiates between vividness, originality, and transformativeness of one's imagination. It should be noted that the vividness factor of the TCIA reflects the ability for persistent and thorough work, as it has shown to correlate with intelligence, and achievement test scores in math and reading.…”
Section: Recommendations For Instrument Selectionmentioning
confidence: 99%